Development of nanosystems for active tumor targeting in photodynamic therapy - Ibarra, Luis Exequiel (2022)
Cancer is one of the major public health problems worldwide. According to the International Agency for Research on Cancer, an estimated 19.3 million new cancer cases and almost 10 million cancer deaths occurred in 2020 [1]. Furthermore, the diagnosis and treatment of cancer have been hampered by the coronavirus disease 2019 (COVID-19) pandemic and it is expected to result in an increased cancer mortality over the next years due to a delay in the diagnoses, and also due to an interruption in the treatments that had been applied to cancer patients. For example, the U.S. National Cancer Institute estimated a 1% increase in deaths related to breast and colorectal cancer over the next 10 years, the equivalent of approximately 10,000 more deaths, due to the impact of the pandemic [2]. This highlights the need to continue in the search of new therapeutic compounds in order to reduce the chance of cancer recurrence after traditional treatments such as surgery and radiotherapy.Some of these new treatments could be used as primary or adjuvant therapeutic options, for instance, photodynamic therapy (PDT) arises as an improved treatment tool due to its highly effective, non-invasive and localized therapeutic action. Taking consideration of the selective action in the irradiation tumor area with PDT, and that it is a treatment that does not compromise other treatment options and presents reduced long-term morbidity when compared with chemotherapy or radiotherapy, this photo-assisted therapy is positioned as a main and/or adjuvant treatment in the fight against cancer. PDT has been approved by the Food Drug Administration (FDA), and also by other regulatory agencies around the world, to treat a variety of tumors and malignancies in the clinic [3]. For the success of PDT, three elements must converge in tumor cells: photosensitizer (PS) accumulation, light irradiation penetration and the presence of molecular oxygen. More of the recent developments regarding PDT have been made around the generation of new PSs.